Penerapan Metode iqro’ dan Pengaruhnya terhadap Kemampuan membaca Al-Qur’an murid MDA Muhammadiyah Bonan Dolok - IHSAN Ihsan Siregar (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2018)
In the teaching Read aloud the Qur'an, there are several methods to achieve the ability to read the Qur'an. Madrasah Diniyah Awaliyah Muhammadiyah Bonan Dolok Padangsidimpuan carries out the teaching of Al-Qur'an Reading. The problem is that students who enroll in Madrasah Diniyah Awaliyah Muhammadiyah Bonan Dolok Padangsidimpuan, not at the same time. So that teachers face difficulties uniform subject matter to students. It also influenced the educational background of the students. who has ever learned to read and write Al-Qur'an and partly derived from State Madrasah Ibtidaiyah which teaches to read Al-Qur'an since class I. Some others have never studied Read Al-Qur'an.Iqro 'method was chosen to be applied at Madni Diniyah Awaliyah Muhammadiyah Bonan Dolok. Hopefully, this method is able to answer the problem of the Qur'anic Teaching and Learning Program at Madrasah Diniyah Awaliyah Muhammadiyah Bonan Dolok Padangsidimpuan.Research results show that teachers use iqro 'book in teaching reading al-Qur'an. The teacher uses Iqro's book in introducing the Hijaiyah characters, introducing the dignity, weeding the letters Hijaiyah, bacan mad (long) and also in teaching the law of tajwid law (rules of rules applicable in reading the Qur'an). In addition, teachers also use the characteristic properties of Iqro 'books in teaching students to be able to read the Qur'an. Teachers often give home reading task which is the nature of CBSA (Active Learning of Students), the teacher gives more assignment to read directly from lecture method, the teacher directs the students to pay attention to the friend who read as application of the nature of the book of Iqro ', the students feel the ease of learning as proof of the practical method of Iqro ', the students also do not easily bored in learning with the nature Iqro' varied.The ability to read the Qur'an of MDA Muhammadiyah Bonan Dolok students shows that students know letters, makhraj, harkat, mad reading and stringing letters Hijaiyah. Besides that also obtained picture that student MDA Muhammadiyah Bonan Dolok also able to read al-Qur'an with correct tajwid.Based on the result of the research, it can be concluded that there is influence of Iqro 'method implementation to the reading ability of the students of MDA Muhammadiyah Bonan Dolok Padangsidimpuan. Keywords: Implementation, iqro 'Method, Influence, Ability to read Al-Qur'an